2017
DOI: 10.1111/tid.12713
|View full text |Cite
|
Sign up to set email alerts
|

Coccidioidomycosis among persons undergoing lung transplantation in the coccidioidal endemic region

Abstract: Within the coccidioidal endemic region, post-transplantation coccidioidomycosis was a definable risk among lung transplant recipients. Use of antifungals appeared to reduce this incidence of disease. Almost all cases resulted in pulmonary disease, suggesting that the lung is the primary site of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In addition, the incidence of coccidioidal infection during the first year was reported at 4.2% after liver transplantation [26] and as 5.8% among lung transplant recipients [27]. In addition, there have been recent reports of an overall increase in the incidence of coccidioidomycosis that may be due to several factors such as an increase in the number of immunosuppressed patients, including organ transplant recipients living in the endemic area [28].…”
Section: How To Minimize the Risk Of Coccidioidomycosis In Solid Orgamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the incidence of coccidioidal infection during the first year was reported at 4.2% after liver transplantation [26] and as 5.8% among lung transplant recipients [27]. In addition, there have been recent reports of an overall increase in the incidence of coccidioidomycosis that may be due to several factors such as an increase in the number of immunosuppressed patients, including organ transplant recipients living in the endemic area [28].…”
Section: How To Minimize the Risk Of Coccidioidomycosis In Solid Orgamentioning
confidence: 99%
“…The incidence of coccidioidomycosis is estimated at 3.8% to 6.9% in solid-organ transplant (SOT) recipients during the early transplantation period, based on published reports of kidney and heart transplant recipients at 3 medical centers in Arizona from 1960 to 2000 [ 24 , 25 ]. In addition, the incidence of coccidioidal infection during the first year was reported at 4.2% after liver transplantation [ 26 ] and as 5.8% among lung transplant recipients [ 27 ]. In addition, there have been recent reports of an overall increase in the incidence of coccidioidomycosis that may be due to several factors such as an increase in the number of immunosuppressed patients, including organ transplant recipients living in the endemic area [ 28 ].…”
Section: How To Minimize the Risk Of Coccidioidomycosis In Solid Orgamentioning
confidence: 99%
“…We screened 548 studies, of which 197 fulfilled criteria [ 2–197 ]. Of these, 4 included a review of related literature [ 2–4 , 198 ], 15 were cohort studies [ 10 , 32 , 47 , 53 , 54 , 56 , 57 , 62 , 63 , 71 , 89 , 100 , 184 , 185 , 187 ], and the majority were case reports. After careful review of references, 1 cohort [ 1 ] and 42 additional case reports or series were identified [ 199–213 ] including 20 [ 188 , 190 , 192 , 214–230 ] from a prior review [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among 16 cohort studies, 3 reported on blastomycosis [ 56 , 62 , 63 ], 5 on coccidioidomycosis [ 10 , 32 , 47 , 53 , 71 ], and 4 on histoplasmosis [ 1 , 54 , 89 , 248 ], and 4 evaluated a mixture of endemic mycoses [ 57 , 184 , 185 , 187 ]. The majority of cohorts were single-institution studies, except for 4 [ 47 , 57 , 184 , 185 ] that involved multiple institutions and included surveillance data [ 184 ], or registry data [ 185 ].…”
Section: Resultsmentioning
confidence: 99%
“… 103 Some experts recommend lifelong suppressive therapy in lung transplant recipients in the endemic. 103 , 158 …”
Section: Introductionmentioning
confidence: 99%